The Santander History Center and the management of local memory from 1934 to 1944: Centennial celebrations of Eloy Valenzuela, Solón Wilches and Vicente Azuero - Samacá Alonso, Gabriel David; Calderón Patiño, Sol Alejandra (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article begins with the construction of social memory and the politics of memory in order to demonstrate how the regions and their intellectual elite turned to eminent regional characters in order to create and strengthen their projects of identity. We seek to demonstrate how the Santander History Center, in compliance with its mission of establishing and disseminating knowledge about the regional past, celebratedthe lives of these three prominent men in regional history in order to position them in the memory of Santander´s citizens as examples of regional pride. The article is structured around the three commemorations: Eloy Valenzuela in 1934, Solón Wilchesin 1935 and Vicente Azuero in 1944. The study concludes that references to these individuals were associated with a set of civic virtues that included: honor, Castilian heritage, modesty, wisdom, adherence to democratic principles, and a progressive,industrial spirit.